Left ventricular rupture: a rare complication and an unusual presentation - Mathew, Antony (BMJ Case Rep, 2020)
Myocardial infarction (MI) is a relatively common medical condition in the community. A rare complication of acute MI is left ventricular rupture (LV) rupture. This usually follows a transmural infarct. The incidence of this is 2%–4% and this usually happens within 3–7 days of MI. The anterolateral wall is involved in the majority of cases. Atypical presentations can occur several weeks after the initial event. Symptoms may mimic gastrointestinal disorder. The prognosis of this condition is very grim. However, with appropriate treatment, they can make an excellent recovery. The definitive treatment for this is surgical repair. We present the case of a 70-year-old man who had LV rupture and his clinical journey.